R&D and the Singapore economy : a case study - Yong, Meei Yun (2014)
The manifestation ofthe destructive powers ofR & D took place in 1945, when the United States President of that regime, commissioned the release of a revolutionary atomic bomb on Hiroshima, Japan. It is also R & D, which is putting Japan back on the road to recovery and becoming an economic superpower. The latter, which is commercial R & D has been adopted by Singapore as an economic turbo-power. As exemplified by empirical findings in the States and Japan, R & D is postulated to contribute to productivity and consequently, Gross National Product (GNP). Amidst various infrastructures and incentives designed to boost R & D in Singapore, IS a comprehensive set of tax incentives catering to profitable R & D ventures. The Singapore Income Tax model is different from those adopted by its Newly Industrializing Countries (NICs) counterparts. This is partly why they offer tax incentives for R & D in varied forms. Nevertheless, the tax incentives encouraging R & D provided by the NICs will be combed. Eventually, several recommendations on building a boisterous environment for R & D were raised in the dissertation. These purported cross-sectoral collaborations, international alliances, widening the scope of tax incentives and increasing the pool of R & D researchers.